2007
DOI: 10.1128/jcm.01599-06
|View full text |Cite|
|
Sign up to set email alerts
|

tcdC Genotypes Associated with Severe TcdC Truncation in an Epidemic Clone and Other Strains of Clostridium difficile

Abstract: Severe Clostridium difficile associated disease is associated with outbreaks of the recently described BI/NAP1 epidemic clone. This clone is characterized by an 18-bp deletion in the tcdC gene and increased production of toxins A and B in vitro. TcdC is a putative negative regulator of toxin A&B production. We characterized tcdC genotypes from a collection of C. difficile isolates from a hospital that experienced an outbreak caused by the BI/NAP1 epidemic clone. Sequence analysis of tcdC was performed on DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
149
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(164 citation statements)
references
References 24 publications
(21 reference statements)
12
149
2
1
Order By: Relevance
“…Future work may reveal insertions or deletions in SDA strains in addition to those previously identified in tcdC (5,32,33,36). Indeed, whereas deletions in tcdC have previously been hypothesized to lead to increased toxin production (33,57,62), findings from a recent study (39) indicated that deletions in tcdC do not predict the biological activity of the PaLoc toxin genes, providing further motivation to identify all sources of genetic variation within the C. difficile genomes that may correlate with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Future work may reveal insertions or deletions in SDA strains in addition to those previously identified in tcdC (5,32,33,36). Indeed, whereas deletions in tcdC have previously been hypothesized to lead to increased toxin production (33,57,62), findings from a recent study (39) indicated that deletions in tcdC do not predict the biological activity of the PaLoc toxin genes, providing further motivation to identify all sources of genetic variation within the C. difficile genomes that may correlate with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature suggests that this considerable truncation of TcdC may impair its negative regulatory function and contribute to the increased toxin production observed in BI/NAP1/027 strains (27,36). Molecular analysis of toxinotype V C. diffi cile has demonstrated a similarly truncated TcdC (61 aa compared with 65 aa in BI/NAP1/027 strains and 232 aa in wild-type TcdC) (15), which may imply hypervirulence for this strain as well.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, PCR ribotype 027 (North America pulsed-field type 1), which has been responsible for the most severe outbreaks around the world, is often reported to have an 18-bp in-frame deletion and ⌬117. Evidently, such genetic changes in the negative regulator have been proposed to be responsible for increased toxin production and hence hypervirulence (9,15), but a clear association with clinical manifestations has not been determined (8,14,16,20). No matter what role tcdC deletions and mutations may have in relation to clinical outcome, the internal in-frame deletion of 18 bp and ⌬117 have been targets for real-time PCR screening for PCR ribotype 027 (4,11,18,21).…”
mentioning
confidence: 99%